Ultrastructural examination of the corticocollicular pathway in the guinea pig: a study using electron microscopy, neural tracers, and GABA immunocytochemistry - Nakamoto, Kyle T.; Mellott, Jeffrey G.; Killius, Jeanette; Storey-Workley, Megan E.; Sowick, Colleen S.; Schofield, Brett R. (Frontiers in Neuroanatomy, 2013)
Projections from auditory cortex (AC) can alter the responses of cells in the inferior colliculus (IC) to sounds. Most IC cells show excitation and inhibition after stimulation of the AC. AC axons release glutamate and excite their targets, so inhibition is presumed to result from cortical activation of GABAergic IC cells that inhibit other IC cells via local projections. However, it is not known whether cortical axons contact GABAergic IC cells directly. We labeled corticocollicular axons by injecting fluorescent dextrans into the AC in guinea pigs. We visualized the tracer with diaminobenzidine and processed the tissue for electron microscopy. We identified presumptive GABAergic profiles with post-embedding anti-GABA immunogold histochemistry on ultrathin sections. We identified dextran-labeled cortical boutons in the IC and identified their postsynaptic targets according to morphology (e.g., spine, dendrite) and GABA-reactivity. Cortical synapses were observed in all IC subdivisions, but were comparatively rare in the central nucleus. Cortical boutons contain round vesicles and few mitochondria. They form asymmetric synapses with spines (most frequently), dendritic shafts and, least often, with cell bodies. Excitatory boutons in the IC can be classified as large, medium or small; most cortical boutons belong to the small excitatory class, while a minority (~14%) belong to the medium excitatory class. Approximately 4% of the cortical targets were GABA-positive; these included dendritic shafts, spines, and cell bodies. We conclude that the majority of cortical boutons contact non-GABAergic (i.e., excitatory) IC cells and a small proportion (4%) contact GABAergic cells. Given that most IC cells show inhibition (as well as excitation) after cortical stimulation, it is likely that the majority of cortically-driven inhibition in the IC results from cortical activation of a relatively small number of IC GABAergic cells that have extensive local axons.